Physical Activity Patterns Among Older Adults With and Without Knee Osteoarthritis in Six European Countries. Issue 2 (February 2016) - Herbolsheimer, Florian; Schaap, Laura A.; Edwards, Mark H.; Maggi, Stefania; Otero, Ángel; Timmermans, Erik J.; Denkinger, Michael D.; Pas, Suzan; Dekker, Joost; Cooper, Cyrus; Dennison, Elaine M.; van Schoor, Natasja M.; et al.
Abstract : Objective: To investigate patterns of physical activity in older adults with knee osteoarthritis (OA) compared to older adults without knee OA across 6 European countries. We expect country‐specific differences in the physical activity levels between persons with knee OA compared to persons without knee OA. A varying degree of physical activity levels across countries would express a facilitating or impeding influence of the social, environmental, and other contextual factors on a physically active lifestyle. Methods: Baseline cross‐sectional data from the European Project on Osteoarthritis were analyzed. In total, 2, 551 participants from 6 European countries (Germany, Italy, The Netherlands, Spain, Sweden, and the UK) were included. Results: Participants with knee OA were less likely to follow physical activity recommendations and had poorer overall physical activity profiles than those without knee OA (mean 62.9 versus 81.5 minutes/day, respectively; P = 0.015). The magnitude of this difference varied across countries. Detailed analysis showed that low physical activity levels in persons with knee OA could be attributed to less everyday walking time (odds ratio 1.31, 95% confidence interval 1.07–1.62). Conclusion: This study highlighted the fact that having knee OA is associated with a varying degree of physical activity patterns in different countries. This national variation implies that low levels of physical activity among persons with knee OA cannot be explained exclusively by individual or disease‐specific factors, but that social, environmental, and other contextual factors should also be taken into account.